LOYALTY REVIEWED FROM ADVERTISING MEDIA BRAND TRUST AND BRAND EQUITY (STUDY ON CUSTOMERS OF TELKOMSEL DATA QUOTA IN SURAKARTA) - Nissa Okta Ayu Harjani; Sudarwati Sudarwati; Sarsono Sarsono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this study is whether advertising media, brand trust, and brand equity have a significant and simultaneously effect on customer loyalty of Telkomsel data quota customers in Surakarta. The population in this study is infinite because of the large number of Telkomsel customers in Surakarta. The research sample was taken by incidental sampling and obtained 100 respondents using the multiple linear regression method. In this study, a questionnaire was distributed to Telkomsel quota customers. The results showed that the variable advertising media, brand trust, and brand equity had a significant effect on Telkomsel data quota customers in Surakarta and advertising media had a positive effect on customer loyalty while partially brand trust had no positive effect on customer loyalty. And for brand equity it had a positive effect on customer loyalty. positive on customer loyalty. Three independent variables explained that customer loyalty was 41,3% and the others were influenced by other variables. Keywords: advertising media, brand trust, brand equity, loyalty